Leptomeningeal Metastasis: The Role of Cerebrospinal Fluid Diagnostics - Bönig, Lena; Möhn, Nora; Ahlbrecht, Jonas; Wurster, Ulrich; Raab, Peter; Puppe, Wolfram; Sühs, Kurt-Wolfram; Stangel, Martin; Skripuletz, Thomas; Schwenkenbecher, Philipp (Frontiers in Neurology, 2019)
Background: Metastatic spread into the cerebrospinal fluid (CSF) represents a severe complication of malignant disease with poor prognosis. Although early diagnosis is crucial, broad spectrums of clinical manifestations and pitfalls of magnetic resonance imaging (MRI) and CSF diagnostics can be challenging. Data is limited how CSF parameters and MRI findings relate to each other in patients with leptomeningeal metastasis. Methods: Patients with malignant cells in CSF cytology examination diagnosed between 1998 and 2016 at the Department of Neurology in the Hannover Medical School were included in this study. Clinical records, MRI findings and CSF parameters were retrospectively analyzed. Results: 113 patients with leptomeningeal metastasis were identified. 76 patients (67%) suffered from a solid malignancy while a hematological malignancy was found in 37 patients (33 %). Cerebral signs and symptoms were most frequently found (78% in solid vs. 49% in hematological malignancy) followed by cranial nerve affection (26% in solid vs. 46% in hematological malignancy) and spinal symptoms (26% in solid vs. 27% in hematological malignancy). In patients with malignant cells in CSF MRI detected signs of leptomeningeal metastasis in 62% of patients with solid and in only 33% of patients with hematological malignancy. Investigations of standard CSF parameters revealed a normal CSF cell count in 21% of patients with solid malignancy and in 8% of patients with hematological malignancy. Blood-CSF-barrier dysfunction was found in most patients (80% in solid vs. 92% in hematological malignancies). Elevated CSF lactate levels occurred in 68% of patients in solid and in 48% of patients with hematological malignancy. A high number of patients (30% in solid vs. 26% in hematological malignancy) exhibited oligoclonal bands in CSF. Significant correlations between the presence of leptomeningeal enhancement demonstrated by MRI and CSF parameters (cell count, lactate levels, and CSF/Serum albumin quotient) were not found in both malignancies groups. Conclusion: CSF examination is helpful to detect leptomeningeal metastasis since the diagnosis can be challenging especially when MRI is negative. CSF cytological investigation is mandatory whenever leptomeningeal metastasis is suspected, even when CSF cell count is normal.